28. Immunogenicity of rVSVΔG-ZEBOV-GP Ebola Vaccine (ERVEBO™) in Participants by Age, Sex, and Baseline GP-ELISA Titer: A Post Hoc Analysis of Three Phase 2/3 Trials. (31st December 2020) - Simon, Jakub; Kennedy, Stephen; Mahon, Barbara; Dubey, Sheri; Grant-Klein, Rebecca; Liu, Ken; Hartzel, Jonathan; Coller, Beth-Ann; Welebob, Carolee; Hanson, Mary; Grais, Rebecca
Abstract: Background: The recent Ebola virus disease (EVD) outbreak in the Democratic Republic of the Congo highlights the sustained threat of EVD morbidity and mortality where healthcare and vaccine delivery are challenging. ERVEBO®, a live recombinant vesicular stomatitis virus (VSV) vaccine containing the Zaire ebolavirus glycoprotein (GP) in place of the VSV GP (rVSVΔG-ZEBOV-GP), was developed by Merck & Co., Inc., Kenilworth, NJ, USA in collaboration with multiple partners to prevent EVD and has been approved for human use in several countries. Methods: We pooled data from three Phase 2/3 clinical trials conducted in Guinea (FLW), Sierra Leone (STRIVE), and Liberia (PREVAIL) during the 2013–2016 West African outbreak to assess immune responses using a validated assay in each of the three studies and performed a post hoc analysis by sex, age (18–50 yrs & >50 yrs) and baseline (BL) GP-enzyme-linked immunosorbent assay (ELISA) titer (< 200 & ≥200 EU/ml). The full analysis set (FAS) population included the primary immunogenicity populations (all vaccinated participants with serology data collected within an acceptable day range) from all three trials. The endpoints were total IgG antibody response (EU/mL) measured by the GP-ELISA and neutralizing antibody response measured by the plaque reduction neutralization test (PRNT) to rVSVΔG-ZEBOV-GP at Days 14, 28, 180, and 365 postvaccination. Results: In the overall population and in all subgroups, GP-ELISA and PRNT geometric mean titers increased from BL, with most peaking at Day 28 and persisting through Day 365. There were differences between males and females and between participants with BL GP-ELISA < 200 & ≥200 EU/ml. There did not appear to be a difference between age groups. Conclusion: These data demonstrate that rVSVΔG-ZEBOV-GP elicits a robust and durable immune response up to 12 months in participants regardless of age, sex, or BL GP-ELISA titer. The higher immune responses observed in females and participants with preexisting immunity are consistent with those described in published literature for other vaccines. Disclosures: Jakub Simon, MD, MS, Merck Sharp & Dohme Corp, a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA (Employee, Shareholder) Stephen Kennedy, MD, Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA (Scientific Research Study Investigator) Barbara Mahon, MD, Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA (Employee, Shareholder) Sheri Dubey, MS, Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA (Employee, Shareholder) Rebecca Grant-Klein, PhD, Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA (Employee, Shareholder) Ken Liu, PhD, Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA (Employee, Shareholder) Jonathan Hartzel, PhD, Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA (Employee, Shareholder) Beth-Ann Coller, PhD, Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA (Employee, Shareholder) Carolee Welebob, PhD, Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA (Employee, Shareholder) Mary Hanson, PhD, Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA (Employee, Shareholder) Rebecca Grais, PhD, Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA (Scientific Research Study Investigator)